2007
DOI: 10.1021/la063347+
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced “Stick−Slip” on Superhydrophilic Semiconductor Surfaces

Abstract: Transparent mesoporous TiO2 (M-TiO2) thin films were prepared on quartz via a reverse micelle, sol-gel, spin-coating technique. Films were characterized by atomic force microscopy (AFM) and Raman and UV-vis spectroscopies and were found to be mostly anatase with low surface roughness (Rt approximately 5 nm). The time dependence of film photoinduced superhydrophilicity (PISH) was measured by observation of the spreading of a sessile water drop using a new, continuous measurement technique wherein the drop was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…These effects are reversed if the light is turned off or if O 2 is removed from the ambient. As can be glean from the Fujishima et al review [2], there is considerable controversy as to the main source of this effect, with groups falling into two camps: (1) those attributing the effect to UV light induced modifications of the TiO 2 surface that facilitate better wetting [1783][1784][1785][1786][1787][1788][1789][1790][1791]; and (2) those attributing the effect to the well-known photooxidation properties of TiO 2 in removing hydrophobic organic adlayers from the TiO 2 surface [740,[1779][1780][1781][1782]. Both sides of this issue have been presented in the Fujishima et al review [2], and need not be repeated here.…”
Section: Photoinduced Hydrophilicitymentioning
confidence: 99%
“…These effects are reversed if the light is turned off or if O 2 is removed from the ambient. As can be glean from the Fujishima et al review [2], there is considerable controversy as to the main source of this effect, with groups falling into two camps: (1) those attributing the effect to UV light induced modifications of the TiO 2 surface that facilitate better wetting [1783][1784][1785][1786][1787][1788][1789][1790][1791]; and (2) those attributing the effect to the well-known photooxidation properties of TiO 2 in removing hydrophobic organic adlayers from the TiO 2 surface [740,[1779][1780][1781][1782]. Both sides of this issue have been presented in the Fujishima et al review [2], and need not be repeated here.…”
Section: Photoinduced Hydrophilicitymentioning
confidence: 99%
“…Therefore, CA measurements on real surfaces that are rough, heterogeneous, reconstructive, or stimuli-responsive are of great importance, though they are complicated. For example, a stick-slip phenomenon has been occasionally observed on various surfaces and with different working liquids [6][7][8][9][10][11][12][13][14][15]. During the measurement of an advancing CA, with the continuous addition of the working liquid, the volume of the droplet increases, whereas the three-phase line sticks, thus the CA increases steadily.…”
Section: Introductionmentioning
confidence: 99%
“…The water CAs release to less than 5 • quickly, in 160 ms. With the introduction of TiO 2 onto the glass substrate, the coating showed obvious anti-fogging performance. Denison et al [47] reported ultra-fast spreading behavior of water droplets on a transparent mesoporous superhydrophilic TiO 2 film prepared by reverse micelle, sol-gel, and spin coating technology. The photo-induced stick-slip behavior on mesoporous TiO 2 can be observed by investigating the spreading of water droplets on the semiconductor surface irradiated by ultraviolet light.…”
Section: Ultra-fast Spreading With Superwettabilitymentioning
confidence: 99%